Neurosurgery perception of Enhanced Recovery After Surgery (ERAS) protocols. (October 2021) - Agarwal, Prateek; Frid, Ilya; Singer, Justin; Zalatimo, Omar; Schirmer, Clemens M.; Kimmell, Kristopher T.; Agarwal, Nitin
Highlights: Most United States neurosurgeons use ERAS protocols for spine cases. Unanticipated ERAS benefits were decreased patient costs and lower ICU admissions. ERAS implementation challenges include EMR integration and protocol standardization. Average ERAS protocol satisfaction was 4.00 +/− 0.81 on a 5-point Likert scale. Abstract: Enhanced Recovery After Surgery (ERAS) protocols are widespread in several fields, particularly general surgery, and attempt to deliver surgical care at a lower cost while also improving patient outcomes. However, few institutions have implemented ERAS protocols in neurosurgery. As such, a survey of neurosurgeons on the current state of ERAS in neurosurgery was conducted to provide insight on scaling the practice nationally. A 15-question survey was designed to assess the implementation of and satisfaction with ERAS protocols at individual institutions. A total of 39 responses were collected from 38 unique institutions. 58.9% (N = 23) reported implementation of neurosurgical ERAS protocols. 52.1% (N = 12) of the responses were neurosurgeons at academic institutions with neurosurgical residency programs. Most neurosurgeons used ERAS protocols for spine cases (N = 23), with only 17.3% (N = 4) employing ERAS protocols for cranial cases. 69.5% (N = 16) of survey participants reported that the design and implementation of ERAS was a multidisciplinary effort across many departments, including neurosurgery, anesthesia, and pharmacy. Decreased costs and intensive care unit (ICU) admission were reported to be unanticipated benefits of ERAS implementation. Unanticipated challenges to implementation of new protocols included difficulties with electronic medical record (EMR) integration, agreement of protocol details amongst stakeholders, uniform implementation of protocols by all neurosurgeons, and lack of adaptability by multidisciplinary staff. Mean department satisfaction with ERAS protocol implementation was 4.00 +/− 0.81 (N = 22) on a 5-point Likert scale.